Pelatihan Hypermedia Berbasis Virtual Reality Bagi Guru Guru MAN 2 Kudus - Achmad Buchori; Noviana Dini Rahmawati; Dina Prasetyowati; Agus Setiawan (Muria Jurnal Layanan Masyarakat, 2022)
This Community Service Activity (PKM) aims to; (1) provide an introduction to teachers at MAN 2 Kudus regarding Virtual Reality learning media as an alternative IT-based learning media and (2) train MAN 2 Kudus teachers to be able to utilize Virtual Reality-based learning media. The methods applied in this service program are the presentation method, the demonstration method, and the practical method. The presentation method is applied in the introduction of hypermedia software using the millelab application, its benefits, and its application in making virtual reality-based media, demonstration methods regarding program operations and practical methods where teachers practice directly making learning media according to their respective subjects with the use of media-based virtual reality. Keywords: Virtual Reality, Technological Innovation, Covid 19 Pandemic